Changes in landscape‐scale tree biodiversity in the north‐eastern USA since European settlement. Issue 3 (27th December 2020) - Vellend, Mark; Thompson, Jonathan R.; Danneyrolles, Victor; Rousseu, François
Abstract: Aim: Despite global biodiversity losses, trends at local and regional scales are context dependent. Recent studies have been criticized for lacking baselines preceding human impacts, and few such studies have addressed the landscape scale. Our aim was to quantify temporal trends in landscape‐scale tree diversity during an unambiguous period of massively increased anthropogenic disturbance and to test the hypothesis that land use can increase landscape‐scale diversity via increased environmental heterogeneity. Location: Eastern USA. Time period: 1620–2008. Major taxa studied: Trees. Methods: We combined data from archival land surveys and modern‐day forest inventories in the north‐eastern USA to quantify tree genus diversity at the scale of towns ("landscapes"). We modelled change in diversity over time as a function of the proportion of the landscape historically converted to agriculture, historical temperature increases and nitrogen deposition, and other abiotic and spatial variables. We also tested for scale‐dependent changes in beta diversity. Results: Overall, tree genus diversity (Shannon and Simpson indices) changed minimally over time on average, but the magnitude of change increased with the maximum historical percentage of the town in agriculture. Other predictor variables had minimal influence. Beta diversity increased over time for nearby pairs of towns and decreased over time for more distant towns. Main conclusions: Forests have regrown on much former agricultural land, and our results support the hypothesis that increased landscape‐scale environmental heterogeneity, attributable to land use, increased tree diversity. Where agricultural land use was uncommon, declines in diversity might be attributable to effects of logging and fire suppression. Even the strongest driver of biodiversity loss at local and global scales (human land use) can lead to increases in biodiversity at the landscape scale, in addition to scale dependence of biotic differentiation versus homogenization.